CONSOLIDATION CHARACTERISTICS OF WEATHERED MIOCENE CLAYSTONE AS A FUNCTION OF SAMPLE SIZE - Purwanto, Joko
CONSOLIDATION CHARACTERISTICS OF WEATHERED MIOCENE CLAYSTONE AS A FUNCTION OF SAMPLE SIZE, Djoko Purwanto, 1992, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. Geometric requirements for modern high speed highways increasingly mean the locating of the alignment over poor ground areas. On the proposed Cikampek-Padalarang Toll Highway some sections of the alignment will involve construction of high embankments, some areas of which will overly some weathered Miocene claystone. Currently a high trial embankment is being constructed over this foundation material to examine the settlement characteristics of this material as well as material used for the embankment. This laboratory study has concerned the examination of the compressibility characteristics of the Miocene claystone. Sampling was carried out by extracting with considerable care large block samples from trial pits dug down into the Miocene deposit. These were then carefully sealed and wrapped before transporting back to the laboratory for testing in consolidation at both large and small sizes for determination of both compressibility and rate of consolidation properties. Classification tests were also carried out to classify and identify the types of soil samples being examined. The classification tests showed the weathered claystone to be a clay of very to extremely high plasticity, high clay content, and with water content determination temperature to a small extent. The claystone was found to be overconsolidated. Consolidation tests were caried out on two sizes of specimen, i.e. standard pedometer (60 mm dia) and 150 mm dia Rowe cell, with both Cv and Cvr being determined along with total settlement. The results showed a very high rate of drainage in the lateral direction compared with the vertical, suggesting a significant preferentially oriented structure. Little difference was noted for either total or rate of settlement between the results for either sample size, indicating that small samples in this case would be representative of mass behaviour, provided good careful sampling was undertaken